The Use of Minimal Pairs in Improving Students’ Vocabulary Mastery of The Fifth Year Students of SDN 018 Rumbai Pesisir - Novri Susanti Suparman (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2019)
Vocabulary plays the most important part in learning a foreign language especially in the early stage of elementary school.Without knowing the vocabulary,students will not be able in the four language skills, such as speaking, reading,listening and writing. The students’ lack of vocabulary make students cannot communicate their ideas as clearly as they would have to. The fifth year students have difficulty to follow English learning if they do not have enough English vocabulary. According to guideline of English teaching, elementary students should master 500 words. Students are not able to construct, even, a simple sentence consisting of subject and predicate. Students are also not be able to pronounce a word correctly,they pronounce a word based on what they see. According to the writer’s observation in the classroom, while teacher explains the lesson, the students prefer to do something else such as drawing, writing and talking to their partner. To use minimalpair exercises as vocabulary development, the writer represented the words in each minimal pairs to teach or reinforce the meaning of vocabulary while practicing thepronunciation of the words. Students can also put the words in meaningful context sentences. The result of the research shows the students’ improvement after using minimal pairs.